2022
DOI: 10.1108/md-08-2021-1060
|View full text |Cite
|
Sign up to set email alerts
|

Obliterating rating distortions: role of rater disposition and rating context

Abstract: PurposeRecent performance appraisal (PA) literature suggests that alongside cognitive biases, rating distortions may stem from rater disposition and PA context. The study investigated the role of social value orientation (rater disposition), PA purposes and rater accountability (PA context) toward rating distortions at both performance levels, i.e. good and poor.Design/methodology/approachThe authors designed an experimental study and elicited data from N = 110 undergraduate students about two video-taped perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 77 publications
1
0
0
Order By: Relevance
“…The present results of non-significant differences for harvest index confirmed the findings of [19,27]. The genotypes showed no response to the environment and confirmed that the studied genotypes were stable for harvest index and thus certified the earlier findings of [15].…”
Section: Irrigatedsupporting
confidence: 92%
“…The present results of non-significant differences for harvest index confirmed the findings of [19,27]. The genotypes showed no response to the environment and confirmed that the studied genotypes were stable for harvest index and thus certified the earlier findings of [15].…”
Section: Irrigatedsupporting
confidence: 92%